McMichael, History On The Web - Using And Evaluating The Internet - Woestman, Kelly (Teaching History: A Journal of Methods, 2007)
As history educators, we are concerned not only with teaching our students how to think historically but also how to find authentic and reliable sources for historical study. The Internet has brought both benefits and challenges to our classroom door as we figure out ways to help our students separate the wheat from the chaff. Because the web is so vast and so complex, our task only continues to get harder. However, Andrew McMichael's History on the Web: Using and Evaluating the Internet provides an excellent starting point for any instructor or student of history from the high school through the graduate level conducting historical research on the web.